Somatostatinergic systems: an update on brain functions in normal and pathological aging - Martel, Guillaume; Dutar, Patrick; Epelbaum, Jacques; Viollet, Cécile (Frontiers in Endocrinology, 2012)
Somatostatin is highly expressed in mammalian brain and is involved in many brain functions such as motor activity, sleep, sensory and cognitive processes. Five somatostatin receptors have been described: sst1, sst2 (A and B), sst3 to 5, all belonging to the G-protein-coupled receptor family. During the recent years, numerous studies contributed to clarify the role of somatostatin systems, especially long-range somatostatinergic interneurons, in several functions they have been previously involved in. New advances have also been made on the alterations of SRIF systems in several brain diseases and on the potential therapeutic target they represent in these pathologies.